Effect of sanhuanghuoxue decoction on the treatment of chronic renal failure - Qiang Wu; Pu Wang; Changhong Wang; Xiangrong Liu; Xue Zhang (Bangladesh Pharmacological Society, 2016)
The aim of this study was to investigate the efficacy of sanhuanghuoxue decoction in the treatment of chronic renal failure by examining the changes in serum creatinine and blood urine nitrogen using rat models. Compared with the control group, which was treated by coated aldehyde oxystarch, the group treated by sanhuanghuoxue showed remarkable decrease in serum creatinine and blood urine nitrogen. The difference was found statistically significant.